Esophagogastric junction outflow obstruction. Issue 9 (12th June 2021) - Bredenoord, Albert J.; Babaei, Arash; Carlson, Dustin; Omari, Taher; Akiyama, Jun; Yadlapati, Rena; Pandolfino, John E.; Richter, Joel; Fass, Ronnie
Abstract: In the Chicago Classification version 4.0 (CCv4), esophagogastric junction outflow obstruction (EGJOO) is manometrically defined as an elevated median integrated relaxation pressure (IRP) and elevated intrabolus pressure (IBP) during supine wet swallows, and persistently elevated median IRP in the upright position. A clinically relevant conclusive diagnosis of EGJOO requires a manometric diagnosis of EGJOO and associated symptoms such as dysphagia and/or chest pain with at least one of the following supportive investigations (pharmacologic provocation, timed barium esophagogram, and/or endoflip). The Chicago Classification is intended for diagnosis of primary esophageal motor disorders, and thus history and endoscopic evaluation are important to exclude conditions (eg, previous surgery, strictures, or masses) that can secondarily generate the EGJOO pattern on HRM. While a manometric finding of EGJOO is often made and can be an early sign of achalasia, more often it is a manometric finding without clinical implications. The proposed changes in CC4.0 have attempted to make the diagnosis more specific, in order to reduce the number of clinically irrelevant diagnoses and avoid confusion by patients and physicians alike. Abstract : Diagnostic pathway for esophagogastric junction outflow obstruction (EGJOO). Abbreviations: IRP, integrated relaxation pressure; TBE, timed barium esophagram.